A method for preparing a lithium-sulfur battery catalyst material

By preparing a catalyst material CoNi-NC, which coordinates the atomically dispersed Ni-Co bimetallic tandem sites in lithium-sulfur batteries, the inefficiency caused by the multi-step conversion chemical process of sulfur in lithium-sulfur batteries is solved, and higher electrochemical performance and cyclic stability are achieved.

CN115832312BActive Publication Date: 2025-03-18UNIV OF SHANGHAI FOR SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211726962.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-03-18
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The multi-step conversion chemical process of lithium-sulfur batteries during charging and discharging leads to inefficiency in battery banking and loss of sulfur electrode active substances, and existing catalysts are difficult to effectively solve the problem of polysulfide shuttle.

Method used

The lithium-sulfur battery catalyst material CoNi-NC, which is coordinated with nitrogen and embedded with porous carbon, was prepared by chemical solution method combined with high temperature calcination method. This method selectively removes metal particles on the surface and retains single atomic sites to achieve bimetallic tandem catalytic action.

Benefits of technology

It significantly improves the electrochemical performance of lithium-sulfur batteries, including higher current density and better cycle stability, and can effectively accelerate the adsorption-catalytic-conversion of polysulfides and improve the charge and discharge capacity and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115832312B_ABST
    Figure CN115832312B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a lithium-sulfur battery catalyst material, which is used to prepare a lithium-sulfur battery catalyst material in which atomically dispersed Ni-Co bimetallic tandem sites are coordinated with nitrogen and embedded in porous carbon, and comprises the following steps: step S1, dissolving Zn(NO3)2·6H2O, Co(NO3)2·6H2O and Ni(NO3)2·6H2O in methanol to form a mixed solution, adding 2-methylimidazole and methanol to the mixed solution, stirring and aging, and then filtering and collecting the precipitate, washing the precipitate and vacuum drying to obtain ZnCoNi-ZIF; step S2, placing ZnCoNi-ZIF in a tubular furnace and heating it to obtain a pyrolysis product, soaking the pyrolysis product, selectively removing metal particles on the surface, and vacuum drying to obtain a lithium-sulfur battery catalyst material CoNi-NC. The present invention also provides a lithium-sulfur battery catalyst material, which is prepared by the above-mentioned method for preparing the lithium-sulfur battery catalyst material. The present invention also provides the application of the above-mentioned lithium-sulfur battery catalyst material in a lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery catalyst materials, and in particular relates to a method for preparing a lithium-sulfur battery catalyst material. Background Art

[0002] Lithium-sulfur batteries have a high theoretical energy density (2600Whkg -1 ), low cost, and environmental protection, and are expected to meet the emerging needs of large-scale energy storage and electric vehicles. At present, the fundamental obstacle to the application of this high energy density system comes from the multi-step conversion chemical process of sulfur during the charging and discharging process. The polysulfide intermediate (Li2S n , 4≤n≤8) are easily dissolved in polar organic solvents in the electrolyte, i.e., the shuttle effect, which will further lead to low coulombic efficiency of the battery and loss of active materials of the sulfur electrode. In addition, the accompanying solid (S8) → liquid (polysulfide) → solid (Li2S2 / Li2S) dual-phase transformation has an inherently large phase change energy barrier, resulting in poor electrochemical kinetics of sulfur chemical reactions in the battery. Chemical adsorption or physical confinement of polysulfides by host materials is a conventional approach to solve the dissolution problem. However, due to the low proportion of host materials in the electrode, these methods can only partially alleviate the shuttle effect. On the other hand, the active electrocatalytic strategy established in recent years can not only effectively improve the redox kinetics, but also provide a fundamental solution to solve the polysulfide shuttle. The catalyzed sulfur redox reaction exhibits faster conversion kinetics, especially the conversion of soluble polysulfides (LiPSs) to insoluble final products.

[0003] Currently, more and more electrocatalysts are being used in lithium-sulfur batteries. However, when evaluating the exact role of catalysts in solving the polysulfide shuttling problem, systematic studies on their kinetics and underlying foundations remain neglected. Classical electrocatalytic processes are often referred to as heterogeneous catalytic reactions, that is, catalyzing a specific reaction rather than a series of reactions, while the electrolytic process of sulfur reduction reactions will be more complicated due to the continuous multi-step reduction reactions of sulfur, and different sulfur species intermediates will be dynamically disproportionately concentrated in the electrolyte solution. In addition, a specific sulfur intermediate simultaneously acts as a reactant and a product for adjacent continuous reduction, indicating that the sulfur species in the electrocatalytic reaction are highly conjugated and coupled. In addition to multi-step conversion reactions, sulfur conversion reactions also involve multiphase transitions because long-chain polysulfides (Li2S x , 4≤x≤8) are soluble, while short-chain polysulfides (Li2S x , 1≤x≤2) is insoluble in the electrolyte. This poses a huge challenge to the design of catalysts.

[0004] To solve the above problems, researchers used multi-metal combinations as active sites to selectively adsorb long-chain polysulfides and catalyze the conversion of short-chain polysulfides, showing the prospects of multi-catalyst systems for lithium-sulfur batteries. These methods provide valuable inspiration for the rational design of lithium battery catalysts, that is, multi-step conversion reactions should be considered. However, the ideal catalyst should have two catalytic centers that can catalyze liquid-liquid conversion reactions in series in one structure. and liquid-solid conversion reactions

[0005] In the related art, atomically dispersed metal sites are prepared by chemical solution method combined with high-temperature calcination, coordinated with nitrogen and embedded in the carbon shell. The prepared atomically dispersed nitrogen coordinated single metal sites (MNC) have become the most promising lithium battery catalysts because of their advantages of maximum atomic utilization and dense active density. Although their activity as lithium-sulfur battery catalysts has been demonstrated, it is still a huge challenge to use a single metal site coordinated with nitrogen to achieve bifunctional activity and stability. Since the sulfur reduction reaction during the discharge process is a continuous multi-step reduction reaction, a single atom can only catalyze a specific reaction rather than a series of reactions, so the battery charge and discharge capacity and cycle stability cannot be effectively improved. Summary of the invention

[0006] The present invention is made to solve the above problems, and its purpose is to provide a method for preparing a lithium-sulfur battery catalyst material.

[0007] The invention provides a method for preparing a lithium-sulfur battery catalyst material, which is used for preparing a lithium-sulfur battery catalyst material in which atomically dispersed Ni-Co bimetallic tandem sites are coordinated with nitrogen and embedded in porous carbon. The method comprises the following steps: step S1, dissolving Zn(NO3)2·6H2O, Co(NO3)2·6H2O and Ni(NO3)2·6H2O in methanol to form a mixed solution, adding 2-methylimidazole and methanol to the mixed solution, stirring and aging, and then collecting a precipitate by suction filtration, washing the precipitate and vacuum drying to obtain ZnCoNi-ZIF;

[0008] Step S2, heating the ZnCoNi-ZIF in a tubular furnace to obtain a pyrolysis product, and after the pyrolysis product is soaked, the metal particles on the surface are selectively removed, and then vacuum dried to obtain the lithium-sulfur battery catalyst material CoNi-NC.

[0009] In the preparation method of the lithium-sulfur battery catalyst material provided by the present invention, it can also have the following characteristics: wherein, in step S1, the mass volume ratio of Zn(NO3)2·6H2O, Co(NO3)2·6H2O, 2-methylimidazole, and methanol is 0.952:0.0233:1.314:50, and the molar ratio of Co(NO3)2·6H2O and Ni(NO3)2·6H2O is the same.

[0010] The method for preparing the lithium-sulfur battery catalyst material provided by the present invention may also have the following feature: wherein, in step S1, aging is performed at room temperature for 24 hours.

[0011] The method for preparing the lithium-sulfur battery catalyst material provided by the present invention may also have the following characteristics: wherein, in step S1, when washing the precipitate, ethanol is used for washing three times, and when vacuum drying is performed, vacuum drying is performed at 60° C. for 12 hours.

[0012] The method for preparing the lithium-sulfur battery catalyst material provided by the present invention may also have the following characteristics: wherein, in step S2, when the ZnCoNi-ZIF is heated in a tubular furnace, it is heated at 1000° C. in an Ar flow for 1 h, and the heating rate is 2° C. / min.

[0013] The method for preparing the lithium-sulfur battery catalyst material provided by the present invention may also have the following characteristics: wherein, in step S2, when the pyrolysis product is soaked, 0.5 mM H2SO4 is used for soaking treatment at 70°C for two times, each soaking time being 24 hours.

[0014] The method for preparing the lithium-sulfur battery catalyst material provided by the present invention may also have the following feature: wherein, in step S2, when selectively removing the metal particles on the surface, the nanoparticles and clusters are selectively removed.

[0015] The method for preparing the lithium-sulfur battery catalyst material provided by the present invention may also have the following feature: wherein, in step S2, vacuum drying is performed at 60° C. for 12 hours.

[0016] The present invention also provides a lithium-sulfur battery catalyst material having the following characteristics, which is prepared by the above-mentioned method for preparing the lithium-sulfur battery catalyst material.

[0017] The present invention also provides application of the above lithium-sulfur battery catalyst material in lithium-sulfur batteries.

[0018] Functions and Effects of the Invention

[0019] According to the preparation method of the lithium-sulfur battery catalyst material involved in the present invention, the atomically dispersed Ni-Co bimetallic tandem site nitrogen coordinated and embedded in the porous carbon core of the lithium-sulfur battery catalyst material CoNi-NC is prepared by a chemical solution method combined with a high-temperature calcination method. The lithium-sulfur battery catalyst material has the morphology of a regular dodecahedron, and has a bimetallic tandem site that can act at different stages of the sulfur reduction and oxidation process. At the same time, the biatomic site tandem can accelerate the adsorption-catalysis-conversion of polysulfides. The lithium-sulfur battery catalyst material of the present invention is applied to the positive electrode material of a lithium-sulfur battery to significantly improve the electrochemical performance of the lithium-sulfur battery. At the same time, the preparation method of the lithium-sulfur battery catalyst material of the present invention is simple in process, the raw materials are easily available, and the prepared lithium-sulfur battery catalyst material is environmentally friendly, has very important practical significance, and has great potential for further industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a schematic flow chart of a method for preparing a lithium-sulfur battery catalyst material in an embodiment of the present invention;

[0021] Figure 2 is an AC-TEM image of a lithium-sulfur battery catalyst material in an embodiment of the present invention;

[0022] Figure 3 is an XRD image of a lithium-sulfur battery catalyst material in an embodiment of the present invention;

[0023] Figure 4 is the XPS spectrum of Co 2p of the lithium-sulfur battery catalyst material in the embodiment of the present invention;

[0024] Figure 5 is the Co k-edge XANES spectrum of the lithium-sulfur battery catalyst material in the embodiment of the present invention;

[0025] Figure 6 is the Fourier transform of the Co k-edge of the lithium-sulfur battery catalyst material in the embodiment of the present invention;

[0026] Figure 7 1 is a cyclic voltammetry curve of a lithium-sulfur battery using different catalyst materials in an embodiment of the present invention;

[0027] Figure 8 yes Figure 7 The Tafel diagram corresponding to the first reduction peak in;

[0028] Fig. 9 yes Figure 7 The Tafel diagram corresponding to the second reduction peak in;

[0029] Fig.10 is the rate performance of using different catalyst materials as electrode materials in the embodiments of the present invention;

[0030] Fig.11 The cycle performance of the embodiments of the present invention using different catalyst materials as electrode materials. DETAILED DESCRIPTION

[0031] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the following examples are combined with the accompanying drawings to specifically illustrate the preparation method of the lithium-sulfur battery catalyst material of the present invention.

[0032] <Example>

[0033] Figure 1 It is a schematic flow chart of a method for preparing a lithium-sulfur battery catalyst material in an embodiment of the present invention.

[0034] like Figure 1 As shown, the preparation method of the lithium-sulfur battery catalyst material of this embodiment is used to prepare a lithium-sulfur battery catalyst material in which atomically dispersed Ni-Co bimetallic tandem sites are coordinated with nitrogen and embedded in porous carbon, comprising the following steps:

[0035] Step S1, dissolving Zn(NO3)2·6H2O, Co(NO3)2·6H2O and Ni(NO3)2·6H2O in methanol to form a mixed solution, adding 2-methylimidazole and methanol to the mixed solution, stirring and aging at room temperature for 24 hours, then filtering and collecting the precipitate, washing the precipitate three times with ethanol, and then vacuum drying at 60°C for 12 hours to obtain ZnCoNi-ZIF.

[0036] In this embodiment, the added amounts of Zn(NO3)2·6H2O, Co(NO3)2·6H2O, 2-methylimidazole and methanol are 0.952 g (3.2 mmol), 0.0233 g (0.08 mmol), 1.314 g (16 mmol) and 50 mL respectively, and the added amount of Ni(NO3)2·6H2O is 0.08 mmol.

[0037] Step S2, placing ZnCoNi-ZIF in a tubular furnace, heating it at 1000°C in an Ar flow for 1 hour, with a heating rate of 2°C / min, to obtain a pyrolysis product, and soaking the pyrolysis product twice with 0.5mM H2SO4 at 70°C, each soaking time is 24 hours, and then selectively removing metal particles with larger surface particle size, such as nanoparticles and clusters, and then vacuum drying at 60°C for 12 hours to obtain the lithium-sulfur battery catalyst material CoNi-NC.

[0038] In this embodiment, the nanoparticles and clusters are selectively removed to retain single atoms and highlight the dual-unit catalyst effect.

[0039] Figure 2 is an AC-TEM image of a lithium-sulfur battery catalyst material in an embodiment of the present invention.

[0040] like Figure 2 As shown, in the lithium-sulfur battery catalyst material CoNi-NC prepared in this embodiment, many single atoms of Co and Ni are generated on the surface of NC.

[0041] Figure 3 It is the XRD image of the lithium-sulfur battery catalyst material in the embodiment of the present invention.

[0042] like Figure 3 As shown, the XRD image shows that the lithium-sulfur battery catalyst material CoNi-NC only detects the characteristic diffraction pattern of graphite carbon, further indicating that Co and Ni are coordinated with N in the form of single atoms rather than forming nanoparticles.

[0043] Figure 4 : is the XPS spectrum of Co 2p of the lithium-sulfur battery catalyst material in the embodiment of the present invention.

[0044] like Figure 4 As shown in the XPS image, no characteristic peak of Co metal is shown at 778.3 eV, and Co 2p peaks are found at 780.7 eV and 796.3 eV. 3 / 2 and Co 2p 1 / 2 Two peaks.

[0045] Figure 5 : is the Co k-edge XANES spectrum of the lithium-sulfur battery catalyst material in the embodiment of the present invention.

[0046] like Figure 5 As shown, the XANES spectrum shows that the Co k-edge X-ray absorption near-edge structure (XANES) confirms that the lithium-sulfur battery catalyst material CoNi-NC sample of this embodiment is mainly composed of Co 2+ composition.

[0047] Figure 6 is the Fourier transform of the Co k-edge of the lithium-sulfur battery catalyst material in the embodiment of the present invention.

[0048] like Figure 6 As shown, the Fourier transform of Co k-edge shows that the peak of lithium-sulfur battery catalyst material is located at This is mainly attributed to the Co-N scattering path. Another peak of lithium-sulfur battery catalyst material is located at This mainly corresponds to the scattering path of Co-Ni.

[0049] In this embodiment, at a scan rate of 0.1 mV s -1Under the condition of high temperature and low humidity, the influence of four catalyst materials, CoNi-NC, Co-NC, Ni-NC and NC, on the CV curve of lithium-sulfur battery in the potential window of 1.8V to 2.8V was tested. Figure 7 1 is the cyclic voltammetry curve of lithium-sulfur batteries using different catalyst materials in the embodiments of the present invention.

[0050] like Figure 7 As shown in the figure, compared with Co-NC, Ni-NC and NC cathodes, the two representative cathode peaks of the lithium-sulfur battery catalyst material CoNi-NC in this embodiment appear at a higher potential and the highest current density. Correspondingly, two anode peaks can also be observed for CoNi-NC at a lower potential and a higher current density.

[0051] Figure 8 yes Figure 7 The Tafel diagram corresponding to the first reduction peak in Fig. 9 yes Figure 7 Tafel diagram corresponding to the second reduced peak in .

[0052] like Figure 8 and Fig. 9 As shown, in the liquid-liquid reaction and liquid-solid reaction In the results, the η values ​​of Co-NC and Ni-NC are different, indicating the effective activity of Ni-NC and Co-NC for the conversion of long-chain polysulfides and short-chain polysulfides, respectively. Therefore, the bimetallic tandem sites of CoNi-NC, a lithium-sulfur battery catalyst material, can play a role in different stages of the sulfur reduction and oxidation process to improve the performance of lithium-sulfur batteries, and the diatomic sites can also accelerate the polysulfide adsorption-catalysis-conversion in tandem.

[0053] Fig.10 is the rate performance of using different catalyst materials as electrode materials in the embodiments of the present invention, Fig.11 The cycle performance of the embodiments of the present invention using different catalyst materials as electrode materials.

[0054] like Fig.10 and Fig.11 As shown in the figure, the electrode prepared by the lithium-sulfur battery catalyst material CoNi-NC in this embodiment shows better rate performance than Co-NC, Ni-NC and NC electrodes. And after long-term testing of 1000 cycles at 2C, 534mAhg -1The specific capacity is retained, and the capacity decay rate per cycle is only 0.021%. Therefore, the lithium-sulfur battery catalyst material CoNi-NC prepared in this embodiment can be used to prepare the sulfur-based composite material CoNi-NC-S for use as the positive electrode of the lithium-sulfur battery, which can effectively improve the rate performance of the lithium-sulfur battery, especially the large current charge and discharge performance, and has good cycle stability.

[0055] Functions and Effects of the Embodiments

[0056] According to the preparation method of the lithium-sulfur battery catalyst material involved in this embodiment, the atomically dispersed Ni-Co bimetallic tandem site nitrogen coordinated and embedded in the porous carbon core can be successfully prepared by a chemical solution method combined with a high-temperature calcination method. The lithium-sulfur battery catalyst material CoNi-NC has a regular dodecahedral morphology, and has a bimetallic tandem site that can act at different stages of the sulfur reduction and oxidation process. At the same time, the diatomic site tandem can accelerate the adsorption-catalysis-conversion of polysulfides. The lithium-sulfur battery catalyst material of the present invention is applied to the positive electrode material of a lithium-sulfur battery to significantly improve the electrochemical performance of the lithium-sulfur battery. At the same time, the preparation method of the lithium-sulfur battery catalyst material of this embodiment is simple in process, the raw materials are easily available, and the prepared lithium-sulfur battery catalyst material is environmentally friendly, has very important practical significance, and has great potential for further industrialization.

Claims

1. A method for preparing a lithium-sulfur battery catalyst material, which is used to prepare a lithium-sulfur battery catalyst material in which atomically dispersed Ni-Co bimetallic tandem sites are coordinated with nitrogen and embedded in a porous carbon core, characterized in that: The following steps are involved: Step S1, dissolving Zn(NO3)2·6H2O, Co(NO3)2·6H2O and Ni(NO3)2·6H2O in methanol to form a mixed solution, adding 2-methylimidazole and methanol to the mixed solution, stirring and aging, and then filtering and collecting the precipitate, washing and vacuum drying the precipitate to obtain ZnCoNi-ZIF; Step S2, placing ZnCoNi-ZIF in a tube furnace and heating it to obtain a pyrolysis product, and after the pyrolysis product is soaked, the metal particles on the surface are selectively removed, and then vacuum dried to obtain a lithium-sulfur battery catalyst material CoNi-NC with atomically dispersed Ni-Co bimetallic tandem sites coordinated with nitrogen and embedded in a porous carbon core. The bimetallic tandem sites can play a role in different stages of the sulfur reduction and oxidation process, and the diatomic site tandem can accelerate the adsorption-catalysis-conversion of polysulfides. Wherein, in step S1, the mass volume ratio of the Zn(NO3)2·6H2O, the Co(NO3)2·6H2O, the 2-methylimidazole, and the methanol is 0.952g:0.0233g:1.314g:50ml, and the molar ratio of the Co(NO3)2·6H2O and the Ni(NO3)2·6H2O is the same, In step S2, the ZnCoNi-ZIF is heated in a tube furnace at 1000°C in an Ar flow for 1 h at a heating rate of 2°C / min.

2. The method for preparing a lithium-sulfur battery catalyst material according to claim 1, wherein: in, In step S1, aging is performed at room temperature for 24 hours.

3. The method for preparing a lithium-sulfur battery catalyst material according to claim 1, wherein: in, In step S1, the precipitate is washed three times with ethanol. When vacuum drying is performed, vacuum drying is performed at 60°C for 12 h.

4. The method for preparing a lithium-sulfur battery catalyst material according to claim 1, characterized in that: in, In step S2, the pyrolysis product is immersed in 0.5 mM H2SO4 at 70°C for two times, each time for 24 hours.

5. The method for preparing a lithium-sulfur battery catalyst material according to claim 1, characterized in that: in, In step S2, when the metal particles on the surface are selectively removed, nanoparticles and clusters are selectively removed.

6. The method for preparing a lithium-sulfur battery catalyst material according to claim 1, characterized in that: in, In step S2, vacuum drying is performed at 60° C. for 12 h.

7. A lithium-sulfur battery catalyst material, characterized in that: The catalyst is prepared by the method for preparing a lithium-sulfur battery catalyst material according to any one of claims 1 to 6.

8. Use of the lithium-sulfur battery catalyst material as claimed in claim 7 in a lithium-sulfur battery.

Citation Information

Patent Citations

  • Co atom-doped polyhedral MOFs (Metal-Organic Frameworks) material as well as preparation method and application thereof

    CN113410481A

  • Bifunctional material capable of adsorbing and catalyzing conversion of polysulfide and preparation method of bifunctional material

    CN114904548A